2002
DOI: 10.1103/physrevlett.89.194102
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a Chaotic Ratchet Using Cold Atoms in Optical Lattices

Abstract: We investigate a new type of quantum ratchet which may be realized by cold atoms in a double-well optical lattice, pulsed with unequal periods. The classical dynamics is chaotic and we find the classical diffusion rate D is asymmetric in momentum up to a finite time t r . The quantum behavior produces a corresponding asymmetry in the momentum distribution which is ''frozen-in'' by dynamical localization provided the break time t t r . We conclude that the cold atom ratchets require Db= h 1, where b is a small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
85
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 19 publications
3
85
0
Order By: Relevance
“…The experimental realization of the QKR has triggered in the last decade an impressive number of studies involving dynamical localization [5,6,7,8,9,10,11], quantum transport [12,13,14,15], ratchets [16,17,18], chaosassisted tunneling [19,20], classical and quantum resonances [21,22,23,24]. Quantum resonances have been used in studies of fundamental aspects of quantum chaos such as quantum stabilization [25] or measurements of the gravitation [26].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental realization of the QKR has triggered in the last decade an impressive number of studies involving dynamical localization [5,6,7,8,9,10,11], quantum transport [12,13,14,15], ratchets [16,17,18], chaosassisted tunneling [19,20], classical and quantum resonances [21,22,23,24]. Quantum resonances have been used in studies of fundamental aspects of quantum chaos such as quantum stabilization [25] or measurements of the gravitation [26].…”
Section: Introductionmentioning
confidence: 99%
“…0. In contrast, for the quantum dynamics, a new and modified form of localization, asymmetric dynamical localization (ADL), was found in [5,6] to arrest the diffusion and ''freeze'' the asymmetry. Hence the relative asymmetry I R t !…”
mentioning
confidence: 99%
“…Previous studies of chaotic Hamiltonian ratchets [4] indicated that directed motion arises if certain symmetries are broken, but persists only in the presence of mixed phase-space dynamics (e.g., a bounded classical phase space with a mixture of regular tori and chaotic regions). The quantitative analysis of the directed current then relies on the details of the classical phase space [2].In [5,6] an alternative theoretical proposal for chaotic but asymmetric momentum diffusion, aimed at a realization with cold atoms in far-detuned pulsed optical lattices, was presented. Experiments with cold atoms in neardetuned, driven optical lattices had already been shown to provide realizations of classical Brownian and dissipative ratchets [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has revealed a wide variety of interesting effects including: dynamical localization [2], quantum resonances (QR) [2][3][4], quantum accelerator modes [5,6], and quantum ratchets [7][8][9][10][11][12][13][14][15]. The latter are quantum mechanical systems that display directed motion of particles in the absence of unbalanced forces.…”
mentioning
confidence: 99%